The little book of bulletproof investing : do's and don'ts to protect your financial life - Stein, Benjamin, 1944- (Little book big profits., 2010)
Two experts in personal finance provide accessible advice for individual investors who are uncertain about their investment and retirement portfolios, and outline the steps required to protect one's money from today's financial calamities.